Bibliometric Analysis of High School Keyword Using VOSviewer Indexed by Google Scholar - Dwi Novia Al Husaeni; Asep Bayu Dani Nandiyanto (Indonesian Journal of Educational Research and Technology, 2023)
Schools are institutions designed for the learning process. The school level is divided into basic education, secondary education, and higher education. The purpose of the school is to develop the potential of students. The purpose of this research is to combine mapping analysis with the VOSviewer application. In addition to VOSviewer, Publish or Perish was also carried out in this study. The keyword used is "High School". Based on search results of 1000 relevant articles published from 2017-2021. Based on the research results, the number of published articles about "high school" has decreased every year. This research is expected to help researchers who will conduct and determine the research theme.